Cold exposure and the cardiovascular system: from physiological adaptation to pathological risk - Li, Yao; Wu, Jiawei; Xu, Yinli; Dong, Junbo; Xing, Bo; Wang, Yiwen; Zhou, Zijun; Sun, Boxuan; Li, Jiahui; Yu, Liming; Wang, Huishan (Frontiers in Physiology, 2026)
Cold stress is the therapeutic paradox of cardiovascular medicine: both an established environmental trigger of acute death and a physiological stimulus for powerful adaptation. In this review, we address this paradox critically. The response to cold challenge, which ranges from sympathetic activation and hemodynamic stress to adaptive brown adipose tissue recruitment and cardiac metabolic remodeling, which can be pathological or protective. We synthesize evidence from specific cardiovascular diseases, such as coronary disease and heart failure, and summarize molecular pathways of metabolic, inflammatory, and electrophysiological effects. Native adaptive mechanisms and their therapeutic potential as templates are also discussed. Through synthesis of these multi-faceted avenues, this article builds upon a theoretical basis to propose a mechanistic model for the seasonal regulation of CVD and to outline emerging, cold-based research avenues.